MODERATING EFFECT OF GREEN TECHNOLOGY ADOPTION ON THE RELATIONSHIP OF SUSTAINABLE OPERATIONS PRACTICES AND SUSTAINABLE OPERATIONAL PERFORMANCE - Musaddag Elrayah; Ooi Chee Keong (Operational Research in Engineering Sciences: Theory and Applications, 2023)
This research endeavors to examine the influence of sustainable operational practices on sustainable operational performance, incorporating the moderating influence of green technology adoption within the Saudi Arabian textile industry. Through the utilization of a self-administered questionnaire, data were acquired from a sample of 250 employees affiliated with textile companies in Saudi Arabia. Employing a cross-sectional study design and quantitative methodology, this investigation employed Partial Least Square (PLS)-Structural Equation Modelling (SEM) for statistical analysis. The outcomes of this analysis revealed that internal lean practices, quality management, customer and supplier integration, and internal business processes exerted positive and statistically significant effects on operational performance. Furthermore, the study disclosed that green technology adoption functioned as a substantive moderator, amplifying the impact of sustainable practices on operational performance. The theoretical contributions of this study lie in its emphasis on the pivotal role of technology in advancing sustainability practices within the Saudi Arabian textile industry. Moreover, the practical implications extend to managerial and stakeholder considerations, advocating for the strategic utilization of technology to enhance operational efficiency while mitigating environmental impact. The research also underscores essential directions for future investigations, proposing a broader industry inclusion for comparative analyses and endorsing a mixed-method approach to deepen insights into technology adoption and sustainability practices across diverse business landscapes.